Risk Perception of Climate Change: Empirical Evidence for Germany - Michael Simora; Manuel Frondel; Stephan Sommer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The perception of risks accruing from climate change is a key factor for individual adaptation and prevention behavior, as well as for the willingness to support climate policy measures. Using a generalized ordered logit approach and drawing on a large data set originating from two surveys among more than 6,000 German households, respectively, we analyze the determinants of the perception of the personal risk that is due to heat waves, storms, and floods. We focus on the role of (damage) experience and objective risk measures for these natural hazards, whose frequency is likely to be affected by climate change. In line with the received literature, our results suggest that the personal experience with adverse events, most notably experienced personal damage, is a strong determinant of individual risk perception.
Keywords: D81; H31; Q54; 330